2020
DOI: 10.2147/prbm.s256551
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Magnitude of Psychological Problem and Associated Factor in Response to COVID-19 Pandemic Among Communities Living in Addis Ababa, Ethiopia, March 2020: A Cross-Sectional Study Design</p>

Abstract: Purpose: COVID-19 pandemic is a World Health Organization day-today work and has a significant crisis on the physical and mental health of humans. However, little is known about the mental health crisis of the pandemic in Sub-Saharan countries. Therefore, this study aimed to determine the magnitude of psychological problems and associated factors among communities living in Addis Ababa, Ethiopia. Methods: A community-based cross-sectional study design was conducted from March 10 to 30, 2020. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 26 publications
6
44
2
Order By: Relevance
“…In the United States, a survey from the Centers for Disease Control and Prevention found a 3 to 4 times increase in the rates of adverse mental or behavioral health conditions relative to one year prior among surveyed adults; and suicidal ideation was signi cantly higher among younger adults (18-24 years) group and unpaid adult-caregivers group [16]. Similar ndings have also been observed in various countries such as Ethiopia, China, and Saudi Arabia indicating the substantial impact the COVID-19 pandemic has on the mental health of individuals [1,32,64]. This is particularly concerning as adolescence is a period of heightened sensitivity to stress [62].…”
Section: Introductionsupporting
confidence: 53%
“…In the United States, a survey from the Centers for Disease Control and Prevention found a 3 to 4 times increase in the rates of adverse mental or behavioral health conditions relative to one year prior among surveyed adults; and suicidal ideation was signi cantly higher among younger adults (18-24 years) group and unpaid adult-caregivers group [16]. Similar ndings have also been observed in various countries such as Ethiopia, China, and Saudi Arabia indicating the substantial impact the COVID-19 pandemic has on the mental health of individuals [1,32,64]. This is particularly concerning as adolescence is a period of heightened sensitivity to stress [62].…”
Section: Introductionsupporting
confidence: 53%
“…15 Assessing the perceived risk and protective behaviors and COVID-19-induced anxiety of the population is crucial to be more effective in prevention and control activities towards the outbreak in this country. 16,17 Therefore, the findings of this study can provide important additional evidence to the existing literature to aid further researchers as well as for the community.…”
Section: Introductionmentioning
confidence: 72%
“…The finding is lower compared to the magnitude reported in Addis Ababa communities, 36%. 17 Similarly, a systematic review and meta-analysis of seventeen articles reported a relatively higher anxiety rate (31.9%) among the general public during the pandemic. 22 However, the prevalence rate varied from 6% to 50%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The magnitude of perinatal depression before the pandemic period in Ethiopia was 25.8% [ 18 ], and psychological distress during the pandemic period at the community level was 66.4% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%